The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1987
DOI: 10.1017/s0003356100028038
|View full text |Cite
|
Sign up to set email alerts
|

Growth and carcass composition of pre-pubertal dairy heifers treated with bovine growth hormone

Abstract: The effects of long-term administration of exogenous growth hormone (GH) on growth and carcass composition of pasture-fed, pre-pubertal dairy heifers were examined. Purified bovine GH (specific activity, 0·78 i.u. per mg) was administered daily for 21 weeks (0·6 mg GH per kg M0·75) to one member of each of 12 sets of twins. GH administration resulted in a significantly higher growth rate (0·58 kg/ day) compared with the control group (0·54 kg/day) and produced a heavier carcass (75·6 kg v. 69·5 kg). However, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
27
1
1

Year Published

1988
1988
2005
2005

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(35 citation statements)
references
References 17 publications
4
27
1
1
Order By: Relevance
“…1985) and cattle (Eisemann et at. 1986;Sandles and Peel 1987) injected with GH. In each of these studies increased liveweight gain was associated with decreased carcass fat.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…1985) and cattle (Eisemann et at. 1986;Sandles and Peel 1987) injected with GH. In each of these studies increased liveweight gain was associated with decreased carcass fat.…”
Section: Discussionmentioning
confidence: 99%
“…None-the-less, the results raise the possibility that maintenance of high plasma GH is necessary to sustain the production increases. In this connection, Peel et al (1985) and Sandles and Peel (1987) reported that increased milk production from dairy cows and increased growth of dairy heifers were not sustained after withdrawal of GH treatment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Les (Ilan et al, 1981;Marounek et al, 1989), virginiamycin (Daenicke, 1988;Skrivanova and Marounek, 1993;Skrivanova et al, 1994), lasalocid (Anderson et al, 1988), avoparcin (Moughan et al, 1989) and aureomycin (Brown et al, 1960) Brumby (1959). Similar results were obtained by Sandles and Peel (1987) in heifers treated with 600 pg bST.kg-l.da!rl. Recombinant bST (25-100 p g .kg-1 .day-1 ) increased the average daily gain of 6-weekold female veal calves by 7.1-10.8% (Kirchgessner et al, 1987 increased in the bST + V group at 10 weeks of age (P < 0.05).…”
mentioning
confidence: 65%
“…O aumento da concentração plasmática de IGF-I verificado nos animais que receberam rbST (34,1% em relação ao controle) corrobora a informação de que a administração exógena de somatotropina resulta em elevação dos níveis plasmáticos (Vernon, 1989), como também constatado por Sandles & Peel (1987), em novilhas; Dalke et al (1992) e Tripp et al (1998), em novilhos confinados; Vestergaard et al (1995), em bezerras; e McLaughlin et al (1993), em ovinos. Os principais efeitos estimulatórios de crescimento do GH são mediados pelas somatomedinas, principalmente IGF-I, sintetizado no fígado e em outros órgãos, podendo atuar tanto no próprio órgão em que foi sintetizado (ação autócrina) ou mesmo em diferentes tecidos (ação parácrina) (Coutinho, 1996).…”
Section: Resultsunclassified